Infectious, inflammatory and neoplastic aspects for making an intestinal elimination stoma - Oliveira, Ane Raquel de; Carneiro, Ana Fagundes; Ribeiro, Wanderson Alves; Pedrosa, Pietro Henrique Benevides; Guedes, Mirian Maria Ferreira; Souza, Érica Motta Moreira de; Pires, Tarsila Reis Pinto; Constantino, Gabriel Nivaldo Brito (Brazilian Journal of Science, 2024)
Intestinal ostomy is a surgical procedure that aims to change the path of effluents by externalizing part of the intestine on the surface of the abdomen. Life habits are factors that contribute to intestinal infections and inflammation, just as cancer is one of the pathologies that most often causes intestinal ostomies. This study aimed to identify, through review research, primary, infectious, inflammatory and oncological diseases that lead to intestinal infections and inflammations, as well as cancer being one of the pathologies that causes the most in ostomized individuals. A bibliographical review study of the literature with a qualitative approach of the descriptive reflective analysis type was carried out. Important points were reached under the influence of Crohn’s disease and its relationship with the creation of an intestinal ostomy; Fournier syndrome related to the reason for creating an ostomy, and for colorectal cancer and the creation of an intestinal ostomy. It is concluded that patients with an intestinal ostomy, whether due to inflammatory diseases such as Crohn’s disease, infectious diseases (Fournier Syndrome) or oncological diseases (colorectal cancer), are increasing due to modifiable factors linked to lifestyle, smoking, sedentary lifestyle, morbid obesity and poor eating habits associated with low water intake.